Bi-doped NaTaO3 photocatalysts for hydrogen production under simulated sunlight: band gap narrowing and structural transitions - Alves, Gustavo Andrade Silva (2021)
In the global scenario of increasing environmental concerns over the dependence on fossil fuels, photocatalytic water splitting has been regarded as a promising method for the clean production of hydrogen fuel (H2) from water and sunlight. Despite recent advancements, only a few materials can be efficiently applied as photocatalysts for this reaction. In this context, sodium tantalate (NaTaO3) is highly active for H2 evolution, although the wide band gap of 4.0 eV precludes its practical application for solar water splitting. Therefore, a variety of band-gap narrowing approaches for this compound have been recently proposed, including bismuth doping. In this work, Bi-doped NaTaO3 with a nanocubic morphology has been obtained through a simple molten salt method, in order that Bi3+-Ta5+ atomic substitutions promote the formation of midgap electronic states which allow the absorption of light from the simulated sunlight spectrum (AM 1.5G). X-ray diffraction results reveal that the orthorhombic perovskite structure of NaTaO3 undergoes a structural transition to pseudocubic upon low-concentration (0.5-4 mol%) Bi-doping. Accordingly, the Bi-doped photocatalysts present considerable H2 evolution under simulated sunlight, whereas pristine NaTaO3 exhibits negligible activity in these conditions. The highest H2 evolution rates are obtained with 3 mol% Bi-doped NaTaO3, as a possible consequence of the conjunction between the narrowed band gap of 3.6 eV with the rectified Ta-O-Ta bond angles in the pseudocubic lattice. Moreover, the photocatalytic activity is further improved and kept stable for 110h of reaction after Ni co-catalysts are loaded onto Bi-doped NaTaO3 by magnetron sputtering deposition, in order that the nanosized Ni particles may provide abundant surface reaction sites for the evolution of H2.